An Investigation of How Digital leadership, Person-Job Fit and Work Commitment Affect Job Performance in Indonesian Public Sector - Prasetyo, Anton; Apidana, Yordan Hermawan (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the relationships between digital leadership and person-job fit on job performance through work commitment as a mediating variable in the public sector context. The research was conducted at BBKKP (Center for Leather, Rubber and Plastic) Yogyakarta, employing a quantitative approach with survey methodology. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that digital leadership significantly influences work commitment but does not directly affect job performance, while person-job fit demonstrates significant effects on both work commitment and job performance. Work commitment emerges as a crucial mediating variable, showing the strongest direct effect on job performance and significantly mediating the relationships between both digital leadership and person-job fit with job performance. This study extends the current understanding of digital leadership effectiveness by demonstrating that its influence on performance operates primarily through employee commitment rather than direct effects, contributing to the growing body of literature on digital transformation in public sector organizations. The findings have important implications for public sector management, suggesting that organizations should focus on building employee commitment as a key mechanism for translating digital leadership initiatives and person-job fit considerations into improved performance outcomes, particularly in the context of digital transformation.